A successful, temporary, pragmatic, emergency management of dislodged crowns - L Z G, Touyz (Journal of Management and Science, 2022)
Full crowns are often used as treatment in dentistry. Dislodgement of a crown may occur at any time if a negative tensile force on the crown allows displacement. Keeping the displaced crown in situ is problematic, as the crown tends to come off the stump,may be lost and or swallowed. Emergency refixing is often not feasible or available. This note suggests an easy, successful,emergency management of temporarily refixing the crown with sugarless chewing gum until the crown can be recemented by a dentist.